Diagnostic Utility of White Cell Count, Serum Bilirubin and C Reactive Protein in Acute and Perforated Appendix (Medical Forum Monthly, 2024)
Objective: To determine the diagnostic utility of white blood cell count (WBC), serum bilirubin and C-reactive protein (CRP) by to determine perforation in acute appendicitis.Study Design: Prospective studyPlace and Duration of Study: This study was conducted at the Surgical Department of PIMS Hospital Islamabad from January 2015 to December 2017.Materials and Methods: This study was conducted on patients undergoing emergency appendectomies. Blood samples were taken from all patients in the first hour of admission for WBC count, serum bilirubin and CRP level and referred to the Hospital laboratory. The appendix specimens submitted in sterile container containing formalin as preservative to histopathology department to assess the inflammatory or perforated appendix as a gold standard. All the data was recorded in the proforma and analyzed by SPSS version 16.Results: Total 190 patients underwent appendectomies during two year period, their mean age was 26.59±8.78 years and males were in majority.23(12.1%) patients were diagnosed with perforated appendix by histological examination. Mean of serum bilirubin, WBC and CRPl evels were significantly higher among perforated appendix as compare to inflammatory appendix (P-value 0.001). Logistic regression analysis with forward selection shows that serum bilirubin, WBC and CRP was significant factors of the perforated appendix according to histopathology findings (p<0.05).Conclusion: It was concluded that WBC, Bilirubin, and CRP are the best diagnostic markers for perforated appendix. Suspected appendicitis patients with significant raised CRP, WBC and bilirubin suggests that the patients are unsuitable for conservative treatment.